Study on the Overall Construction of Mountainous Town based on the Concept of The Sponge City - Mi Jun; Luo Yulin (MATEC Web of Conferences, 2018)
The emergency and significance of the development and construction of sponge cities have become a national issue, and it is urgent to deal with irrational problems and disorganization emerged in the construction of sponge city. Due to the complexity of constructing sponge cities, the macroscopic town planning should be put in the first place, and controlling objects are made in accordance with cities’ different characteristics. Then details in technologies in building sponge cities should be organize.